Tuning the morphology of chevron-type graphene nanoribbons by choice of annealing temperature - Cao, Yun; Qi, Jing; Zhang, Yan-Fang; Huang, Li; Zheng, Qi; Lin, Xiao; Cheng, Zhihai; Zhang, Yu-Yang; Feng, Xinliang; Du, Shixuan; Pantelides, Sokrates T.; Gao, Hong-Jun (Nano Research, 2018)
Bottom-up synthesis of graphene nanoribbons (GNRs) by surface-assisted polymerization and cyclodehydrogenation of specifically designed precursor monomers has been shown to yield precise edges and doping. Here we use a precursor monomer containing sulfur atoms to fabricate nanostructures on a Au(111) surface at different annealing temperatures. The nanostructures have distinct configurations, varying from sulfur-doped polymers to sulfur-doped chevron-type GNRs (CGNRs) and, finally, pristine graphene nanoribbons with specific edges of periodic five-member carbon rings. Non-contact atomic force microscopy provides clear evidence for the cleavage of C–S bonds and formation of pristine CGNRs at elevated annealing temperatures. First-principles calculations show that the CGNRs exhibit negative differential resistance. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-03-20
Keywords: chevron-type graphene nanoribbon; C–S bond cleavage; first-principles calculations; negative differential resistance; noncontact atomic force microscopy (NC-AFM); scanning tunneling microscopy (STM)